Time Well Spent: Patient Industry and Occupation Data Collection in Emergency Departments - Taylor, Jennifer A. (J Occup Environ Med, 2017)
OBJECTIVE: No comprehensive national system tracking work-related diseases and injuries exists in the United States. Industry and occupation (I/O) are the missing data elements that would make existing healthcare data useful for occupational health. The authors previously petitioned the National Uniform Billing Committee (NUBC) to adopt I/O standards for states to consider during their healthcare data rulemaking processes. METHODS: The NUBC asked for a pilot study to ascertain the potential burden. The time and cost to ask I/O questions in two hospital emergency departments was evaluated. RESULTS: Asking four I/O questions required 48 seconds on average and cost between $520 and $623 per Registrar per year. The annual cost for the two hospitals to gather I/O on every patient was $4160 and $15,000. CONCLUSIONS: We conclude no undue burden compared with the estimated $250 billion cost of occupational illnesses and injuries.